Problems encountered during the start-up of up flow anaerobic sludge blanket reactors (UASB) at 20 â°C & 15 â°C - Ali, Masood Abdusalam Ghanem (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
UASB technology has been widely adopted for the treatment wastewaters in warm climates. Operation at low temperature wastewaters still present some challenges. When working at lower temperatures a number of operational problems were experienced associated with the accumulation of biogas and wastewater solids in or below the sludge bed. Physical entrapment of the biogas produced formed a buoyant plug, which had a tendency to float the sludge bed. An operational solution to this problem was found which involved fluidising the bed once a day to ensure better distribution of organic solids and allow the release of any trapped biogas. This was achieved by pumping biogas directly from the reactor headspace back up through the bed for a period of 4 minutes, then allowing the bed to settle for a short period (< 10 minutes) before allowing the effluent to discharge. This mode of operation has not been previously been reported and represents a valuable low-energy approach to dealing with high solids wastewaters of this type at low operating temperatures. The results confirmed that full flow treatment under ambient conditions, without heating of the UASB reactor, was feasible.